INVESTIGATING THE SOIL STRESS LEVELS FOR DIFFERENT PILE GEOMETRIES UNDER DIFFERENT LOADING CONFIGURATIONS - Rademan, Daniel; Markou, George (My University, 2023)
The high complexity of investigating the mechanical response of reinforced concrete pile foundations embedded in different soil domains is well known, thus not allowing a deep understanding of the overall structural and geotechnical response of the foundation system. This study investigates the Soil-Structure-Interactions (SSI) and the development of stress levels for different pile configurations under different imposed lateral displacements and superstructural loads. SSI has a significant effect on the lateral resistance of pile groupings that assume two or more piles. The state-of-the-art 3D detailed numerical investigation performed in this research work foresaw an investigation of the effects that pile groupings under imposed lateral displacement have on soil stresses and the overall response of the soil and foundation system. An in-depth study of the resulting stress regions and levels in the soil medium was performed for different loading configurations. The study concluded that the base reaction is proportional to the imposed displacement and the number of piles in the grouping, while the geometry of the foundation system significantly affects the soil stress development. Finally, when torsion is developed at the level of the foundation system, a significantly complicated deformation field derives that requires an advanced modelling approach to objectively and accurately investigate the overall mechanical response of the soil and foundation domains.
Keywords: Soil-structure-interactions; Finite element method; Numerical investigation; Pile groupings; Reinforced Concrete